Subsurface Characterization Using Electrical Resistivity Method: A Case Study of The Bhayangkara Area, Papua, Indonesia - Erwin, Erwin; Virman, Virman` (Westscience Press, 2025)
This study aims to identify the potential and distribution of groundwater aquifers in the Bhayangkara Complex area, Jayapura City, Papua, Indonesia, using the geoelectric resistivity method with a Schlumberger configuration. Increasing demand for clean water and limited surface water availability in Jayapura City make groundwater exploration a strategic alternative to support sustainable water supply. Geoelectric measurements were conducted at three survey lines with different orientations and electrode spacings to obtain subsurface resistivity data. Field data in the form of electric current and potential difference were processed to calculate apparent resistivity values and subsequently inverted using IPI2Win software to obtain true resistivity models. The interpretation was carried out by correlating resistivity values with lithological characteristics and regional geological conditions. The results indicate that each measurement point consists of six subsurface layers with varying resistivity values. Potential groundwater-bearing zones (aquifers) were identified at the fifth layer of all three measurement points, with resistivity values ranging from 0.5 to 300 ohm·m, depths between approximately 20.2 and 70.8 meters, and layer thicknesses from 9.94 to 37.5 meters. Among the three locations, measurement point 03 is recommended as the most suitable site for groundwater drilling due to its relatively shallow aquifer depth and adequate thickness. These findings demonstrate that the geoelectric resistivity method with Schlumberger configuration is effective for groundwater exploration and can serve as a reliable basis for groundwater development planning in urban areas with limited surface water resources.